The Effect of Flexible Work Arrangement and Work-Life Balance on Work Engagement and the mediating Role of Work-Family Conflict - Boukhzam, Caroline (2022)
This research explores the effect of flexible work arrangements and work life balance on work engagement. The study also investigated the mediating effect of work-family conflict. Drawing on the conservation of resource theory and social exchange theory, a conceptual model is developed and the hypotheses linking flexible work arrangements, work-life balance, work engagement and work-family conflict are derived. This study suggests that flexible work arrangement is positively associated with work-engagement, and lack of work-life balance increases work-family conflict which in turns negatively impact work engagement. Quantitative empirical research was conducted to test the conceptual model. The structural model was tested using the Smart PLS software. The outcome of this study reveals that flexible work arrangement positively relates to work engagement. In addition, it was also established the absence of work-life balance leads to work-family conflict which further impact work engagement very detrimentally. Based on these outcomes, our study recommends that human resources managers interested in increasing work engagement levels among their employees should consider introducing and implementing flexible work arrangement strategies. Such an initiative, along with the presence of work-life balance among employees, can potentially minimize the work-family conflict and engage employees to be more engaged in their tasks.